AI alignment is all your need for future drug discovery - Li, Chunyan (Frontiers in Artificial Intelligence, 2025)
In recent years, the integration of artificial intelligence (AI) with drug discovery has become a promising frontier in biomedical research. However, as artificial intelligence systems become increasingly complex, ensuring their alignment with human values and goals becomes essential. Specifically, combining artificial intelligence systems with human values is crucial for reducing potential risks in the field of drug discovery and maximizing social benefits. This article explores the concepts and challenges related to alignment with artificial intelligence in the context of drug discovery, emphasizing on human-centered approaches to AI development and deployment. We further investigated popular technology frameworks designed for human-centered AI alignment, aimed at improving the robustness and interpretability of AI models. We provide some insights into the challenges of human-centered AI alignment, which represents a significant advancement in addressing robustness and interpretability, thus taking a step forward in the field of AI alignment research. Finally, we discuss strategies for systematically integrating human values into AI-driven drug discovery systems. This article aims to emphasize the importance of AI alignment as a foundational principle in the field of drug discovery and advocate the perspective that “AI alignment is all your need for future drug discovery”.